Methodology for Diagnostics of Transformers and D.C. Electric Machines - I. I. Branovitsky; P. D. Matskevich; I. T. Skurtu (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers methods for testing electric power equipment with reference to power transformers and electric direct current machines by measuring complex of their parameters. The above-mentioned methods have been realized in the devices DST-1M and IPEM, respectively.An influence of inductive and capacitive elements included as components of low frequency filters in a measuring device on a value of an extra phase displacement between measured input currents and voltages being caused by them has been analyzed in the paper. The paper reveals that the extra phase displacement is initiated by oscillations of actual inductive and capacitive element values relative to their nominal values. Dependence of root-mean-square deviation of power measurement error due to phase displacement angle under load conditions at various tolerance values of the indicated elements and distribution of actual values of their nominal ones within these tolerances according to a normal low   has been calculated in the paper